About Professional-Communicative Competence Development Among Students-Foreigners At Practical Lessons In Russian As A Foreign (Using The Example Of The Lesson “Tasks And Functions Of Public Relations”) - Sergej S., Khromov (2019)
The development of professional and communicative competence is the most important university task. That is why the training of foreign students in a university should be focused on practical knowledge of the Russian language. This article provides the fragment “Tasks and functions of public relations” of the textbook “Training of professional activity in Russian for foreign students studying Public Relations” (by L.V. Adonina, S.V. Lazarev, S.V. Smirnova, O.S. Fisenko)” [12].